The Effect of the Covid 19 Pandemic on the Online Learning Process - Dendik Dwi Prandika; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
This study aims to determine the effect of the COVID-19 pandemic on the process of utilizing online learning. The informants consisted of 10 primary school teachers of Muhammadiyah 1 gempol. The implementation of online learning uses case studies with a qualitative approach. The results of this study revealed that inadequate facilities and infrastructure, less than optimal delivery of material, the burden of purchasing internet quota, internet connection that sometimes becomes slow, learning styles that tend to be visual, and the teacher's lack of flexibility in controlling student activities Learning at Muhammadiyah 1 Gempol Elementary School in this study uses online learning or commonly referred to as distance learning (from home) with the guidance of parents and teachers at school. Students do online learning and interact with teachers using several applications used such as Google Classroom, Zoom, Google Meet and Whatsapp Group.